2016
DOI: 10.1007/s12038-016-9659-0
|View full text |Cite
|
Sign up to set email alerts
|

CSFV proliferation is associated with GBF1 and Rab2

Abstract: The Golgi apparatus and its resident proteins are utilized and regulated by viruses to facilitate their proliferation. In this study, we investigated Classical swine fever virus (CSFV) proliferation when the function of the Golgi was disturbed. Golgi function was disturbed using chemical inhibitors, namely, brefeldin A (BFA) and golgicide A (GCA), and RNA interfering targets, such as the Golgi-specific BFA-resistance guanine nucleotide exchange factor 1 (GBF1) and Rab2 GTPases. CSFV proliferation was significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…Several viruses of the Picornaviridae , Coronaviridae , and Flaviviridae families rely on GBF1 for their replication (Belov et al, ; Carpp, Rogers, Moritz, & Aitchison, ; Goueslain et al, ; Lanke et al, ; Liang, Zheng, Bao, & Zhang, ; Qin et al, ; van der Linden et al, ; Verheije et al, ; Wang, Du, & Jin, ). However, it has been shown that GBF1 is not involved in the formation of poliovirus, mouse hepatitis coronavirus, and HCV replication complexes but rather in their maturation or activity (Belov et al, ; Goueslain et al, ; Verheije et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several viruses of the Picornaviridae , Coronaviridae , and Flaviviridae families rely on GBF1 for their replication (Belov et al, ; Carpp, Rogers, Moritz, & Aitchison, ; Goueslain et al, ; Lanke et al, ; Liang, Zheng, Bao, & Zhang, ; Qin et al, ; van der Linden et al, ; Verheije et al, ; Wang, Du, & Jin, ). However, it has been shown that GBF1 is not involved in the formation of poliovirus, mouse hepatitis coronavirus, and HCV replication complexes but rather in their maturation or activity (Belov et al, ; Goueslain et al, ; Verheije et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…GBF1 also participates in Golgi morphogenesis and lipid droplet metabolism (Jackson & Bouvet, ). In addition, GBF1 is hijacked by several positive‐strand RNA viruses including Picornaviridae , Coronaviridae , and Flaviviridae members for their replication (Belov et al, ; Carpp et al, ; Goueslain et al, ; Lanke et al, ; Liang et al, ; Qin et al, ; van der Linden et al, ; Verheije et al, ; Wang et al, ). For instance, GBF1 was shown to interact with poliovirus and coxsackievirus B3 (CVB3) non‐structural protein 3A (Wessels et al, ; Wessels et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…This result suggests that AIF1 has a positive effect on CSFV Shimen infection in macrophages. Many cytokines of host maybe affect CSFV replication (Liang et al, 2016), and we considered AIF1-mediated microenvironment in PAM 3D4/21 cells contributed to CSFV Shimen infection. However, more detailed studies are required to consider this finding, and whether the AIF1 could inhibit other viruses also needs further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of influenza (61, 62) and vesicular stomatitis viruses (VSV) (63, 64) the COPI/Arf1 complex seems to play a role in their entry process. Moreover, for VSV as well as for hepatitis C virus (6567), mouse hepatitis coronavirus (68), chikungunya virus (69), poliovirus (57, 58, 70), coxsackievirus (71) and classical swine fever virus (72), COPI/Arf1 has been shown to be necessary for genome replication as well as for viral protein expression. COPI/Arf1 has also been shown to be critical for viral particle assembly of influenza and the Chandipura virus (62, 73).…”
Section: Discussionmentioning
confidence: 99%